KOMPETENSI LULUSAN PENDIDIKAN DASAR DAN PERMASALAHAN - Rizki Ananda; Ayu Supia, Yuyun; Trisya Anjani; Mei Dinda Anggiani; Wardana Surya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study explores the competencies of primary education graduates and the challenges encountered in achieving them. Graduate competency serves as a critical indicator of the success of the primary education system. However, issues such as low teaching quality, inadequate learning facilities, and unequal access to education remain prevalent. This study adopts a qualitative approach through literature review to identify the factors influencing graduate competency. The findings indicate that improving graduate competency requires a relevant curriculum, enhanced teacher quality, and equitable distribution of educational resources.